Lipidomic and Transcriptomic Analysis of the Longissimus Muscle of Luchuan and Duroc Pigs - Zhang, Zhiwang; Liao, Qichao; Sun, Yu; Pan, Tingli; Liu, Siqi; Miao, Weiwei; Li, Yixing; Zhou, Lei; Xu, Gaoxiao (Frontiers in Nutrition, 2021)
Meat is an essential food, and pork is the largest consumer meat product in China and the world. Intramuscular fat has always been the basis for people to select and judge meat products. Therefore, we selected the Duroc, a western lean pig breed, and the Luchuan, a Chinese obese pig breed, as models, and used the longissimus dorsi muscle for lipidomics testing and transcriptomics sequencing. The purpose of the study was to determine the differences in intramuscular fat between the two breeds and identify the reasons for the differences. We found that the intramuscular fat content of Luchuan pigs was significantly higher than that of Duroc pigs. The triglycerides and diglycerides related to flavor were higher in Luchuan pigs compared to Duroc pigs. This phenotype may be caused by the difference in the expression of key genes in the glycerolipid metabolism signaling pathway.